2019
DOI: 10.1038/s41568-019-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternative tumour-specific antigens

Abstract: The role of tumour-specific antigens (TSAs) as targets of anticancer immunity was first recognized in the last century, with studies of TSA-based vaccines becoming more prevalent in the past decade 1-3 (Box 1). Neoantigens are defined here as a subset of TSAs generated by non-synonymous mutations and other genetic variations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
241
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(242 citation statements)
references
References 202 publications
0
241
0
1
Order By: Relevance
“…Interestingly, it has been found that some human cancer-specific antigens, silent in normal tissues, are translated from alternative open reading frames (AltORFs) (Wang et al, 1996(Wang et al, , 1998Rosenberg et al, 2002;Mandic et al, 2003;Slager et al, 2003). These neoantigens are promising targets for the development of antitumour immunotherapies with a potentially broader coverage of patients (Smith et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been found that some human cancer-specific antigens, silent in normal tissues, are translated from alternative open reading frames (AltORFs) (Wang et al, 1996(Wang et al, , 1998Rosenberg et al, 2002;Mandic et al, 2003;Slager et al, 2003). These neoantigens are promising targets for the development of antitumour immunotherapies with a potentially broader coverage of patients (Smith et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The successful clinical implementation of checkpoint inhibitors and CAR-T cells in the routine treatment of various tumor entities has heralded a new era of immunotherapies in cancer [108,109]. Tumor-specific neoantigens derived from fusion oncogene breakpoint regions have attracted great scientific interest for many years, especially as an alternative to singlenucleotide variant-derived tumor-specific antigens [110]. Recently, gene-fusion-derived neoantigens were found to induce tumor-specific T cells and facilitated a complete response in a head and neck-cancer patient treated with immune checkpoint inhibitors despite an overall low tumor mutational burden [111].…”
Section: Targeting Fusion Oncoprotein-specific Neoantigens By Immunotmentioning
confidence: 99%
“…We propose that two elements should be taken into consideration. First, we believe that searches limited to exonic TSAs considerably underestimate the diversity of the TSA repertoire (47). According to initial analyses of primary acute lymphoblastic leukemia samples, the vast majority of TSAs are aeTSAs derived from unmutated allegedly non-coding sequences.…”
Section: Low Accuracymentioning
confidence: 99%